2007
DOI: 10.1590/s0004-282x2007000400006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of seizures and associated factors in children under five living in a deprived municipality of southern Brazil

Abstract: Prevalence of seizure in this deprived population is extremely high and related to socio-economic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
3
5
1
1
Order By: Relevance
“…Similar findings were observed by Abib et al (p=0.03). 15 In the present study, statistically it was also found that seizure disorder is not significantly (p=0.49)among study subjects having Cattle shed nearby house in comparison to subjects not having cattle shed nearby house. Results of present study were in contrast with the study by Montano et al (p=0.001).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Similar findings were observed by Abib et al (p=0.03). 15 In the present study, statistically it was also found that seizure disorder is not significantly (p=0.49)among study subjects having Cattle shed nearby house in comparison to subjects not having cattle shed nearby house. Results of present study were in contrast with the study by Montano et al (p=0.001).…”
Section: Discussionsupporting
confidence: 50%
“…Statistically it was also found that subjects with seizure disorder was not significant (p=0.9988) among study subjects having kachcha house in comparison to subjects without kachcha house, In contrast to study of Abib et al (p=0.1). 15 In present study, it was found that subjects with seizure disorder was not statistically significant among study subjects water supply from non-piped source in comparison to subjects having piped water source. Similar findings were observed by Abib et al (p=0.03).…”
Section: Discussioncontrasting
confidence: 46%
“…Similarly, El-Motayam [ 15 ] found a prevalence of 7–10/1000 among school children below the age of 15 years, while higher rates reported by Shawki and colleagues [ 16 ] who found that the prevalence of epilepsy among school children (≤ 12 years of age) was 12.9/1000 in Upper Egypt, Asyut Governorate. Egyptian studies are much lower than that reported among 5-year-old Brazilian children (45.2/1000) [ 17 ] and among 12-year-old school children in Tahran (32.4/1000) [ 18 ]. This high prevalence reported in the Brazilian and Tahran studies could be explained by difference in the adopted definition of epilepsy where both studies recorded lifetime prevalence of seizure (LPS) not for epilepsy, and they did not necessitate seizure recurrence.…”
Section: Discussionmentioning
confidence: 83%
“…29 Differently from our study, this one was performed in one single section of the city, considered very poor. In other two epilepsy population surveys developed in southeast Brazil (São Paulo), it was observed, in children aged from 0 to 4 years, a lifetime prevalence of epilepsy of 2.8 per 1,000 children, and of active epilepsy of 2.3 per 1,000 children, which was a little lower than the outcomes reported in our study.…”
Section: Rr (Raw) Rr (Adjusted)mentioning
confidence: 83%